Eksistensi Perhimpunan Pemilik dan Penghuni Satuan Rumah Susun (PPPSRS) dalam Kewenangan Pengelolaan Rumah Susun Sewa - Nuraini Zachman; Nur Fauzia (Wajah Hukum, 2021)
Flats are a response to the needs of housing for the community and become an alternative choice for providing ideal housing for developing countries. The purpose of research and writing of this scientific paper through the normative approach method is to analyze the Activities of Management of Flats by the Management Agency, the existence of the Association of Owners and Occupants of Apartment Units (PPPSRS), Voting Rights Related to the Authority of Management and Management of Rental Flats compared to Management of Flats Commercial. In this study using an empirical juridical approach because the researcher was carried out directly on the manager of the rental apartment. The scope of this research is the management of flats and its objects are flats in urban areas. The materials used are field materials and library materials. The data collection technique is document study and the analysis technique is qualitative analysis. The activity of managing the apartment is obliged to be the manager of a legal entity, namely the Association of Owners and Residents of Apartment Units which have been made a legal deed by the Regent or Mayor of the Level II Region and the determination of the voting rights of these members has not been fully realized. Management of simple rental apartments is required by Technical Management Unit (UPT), while Management of Commercial Flats is the Management Body of Commercial Flats, which is the Association of Owners and Occupants of Flat Units, developer as a temporary Management Agency.